Multiple electrode aggregometry and thromboelastography in thrombocytopenic patients with haematological malignancies - Opheim, Elin N. (Blood Transfus, 2019)
BACKGROUND: In thrombocytopenic patients better assessment of bleeding risk than that provided by platelet count alone is required. Multiplate(®) aggregometry and thromboelastography (TEG) could be used, but information on their role in such patients is limited. The primary aim of this study was to investigate the feasibility of Multiplate(®) analyses in patients with haematological malignancies. A secondary aim was to explore whether a multiple logistic regression model combining Multiplate(®), TEG, clinical and laboratory variables was associated with risk of bleeding. MATERIALS AND METHODS: This was an exploratory, prospective observational study of thrombocytopenic patients with haematological malignancies. Total platelet count (TPC), white blood cell count, C-reactive protein (CRP) level, temperature and bleeding status were recorded daily. TEG and Multiplate(®) analyses with four agonists were performed on weekdays. RESULTS: Ten patients were enrolled into the study. The median number of days in a study period was 21. Bleeding was observed on 64 of 298 study days. TPC <20×10(9)/L and <10×10(9)/L occurred on 119 and 25 days, respectively. When TPC was <33×10(9)/L, many samples showed no aggregation, regardless of bleeding status. Despite this, the odds of World Health Organization (WHO) grade 2 bleeding decreased significantly as aggregation increased and Multiplate(®) had a negative predictive value (NPV) of 96% and a positive predictive value (PPV) of 19% for significant bleeding. In the multiple logistic regression model collagen-activated Multiplate(®) aggregation, TEG angle, TEG reaction time and CRP significantly affected the odds of WHO grade 2 bleeding. The combined model had a NPV of 99% and a PPV of 19%. DISCUSSION: Our findings suggest that the markers of platelet function and haemostasis provided by Multiplate(®) aggregometry and TEG may add information to support prediction of bleeding, although platelet count still remains the most accessible analysis for routine testing.